(untitled) (Bangladesh Journal of Anatomy, 2015)
Objective: The umbilical cord is fetal organ and contains two arteries and one vein covered by connective tissue called Whartons jelly. Gestational diabetes mellitus (GDM) is a common metabolic disorder, the importance of which includes possible fetal and maternal complications. As the umbilical cord is the communicating channel between the fetus and the placenta, any pathological change in the umbilical cord may cause harm to the fetus. For this reason, some gross morphological and microscopic features of umbilical cord were analyzed in case of pre-gestational and gestational diabetes mellitus. Materials and Methods: A cross-sectional, analytical and observational type of study was carried out in the Department of Anatomy, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka between July 2004 and December 2005. Total 60 umbilical cords with placentae were collected within 34 to 40 weeks of gestation from BSMMU and BIRDEM. Among these, twenty were from mothers not suffering from diabetes (Control group), twenty had pre-gestational diabetes mellitus (PDM group) and twenty were suffering from gestational diabetes mellitus (GDM group). Number of umbilical vessels were observed on the cut surface of umbilical cord later confirmed by histological examination. Presence or absence of true or false knots were noted. The umbilical cord cross sectional area, vessel areas and their luminal area were estimated. The ANOVA post-hoc option was used for statistical analyses of results. Results: Among the gross and histomorphological variables of the umbilical cord, there was no significant difference between the three groups. DOI: http://dx.doi.org/10.3329/bja.v12i1.22615 Bangladesh Journal of Anatomy, January 2014, Vol. 12 No. 1 pp 25-29